Implementation of Volatility Model in Modeling Relationship Between Share Trade Variables - Valentika, Nina; Waryanto, Hendro (Universitas Pamulang, 2021)
This study deals with the comparison of Generalized Autoregressive (GARCH) models and square returns in analyzing the relationships between stock trading variables. Stocks that have a statistically significant relationship between volume and volume return squared (volatility) cannot be grouped based on the average monthly market capitalization. Based on causal and contemporary models, it is indicated that intraday trading of LQ-45 stock samples is following the theory of the sequential information arrival hypothesis (SIAH) when using the quadratic return model. When viewed from a contemporary basis, this research uses the quadratic return volatility model following Valentika et.al (2017) research using the GARCH volatility model. If viewed from a causal basis, this research that uses the quadratic return volatility model conflicts with the Valentika et.al (2017) study using the GARCH volatility model.